Karakteristik Penanda Kohesi Gramatikal dan Kohesi Leksikal Pada Wacana Iklan Kosmetik Kecantikan Wajah Jepang - Wiyatasari, S.S., M.Hum., Reny (Vocational College of Diponegoro University, 2024)
The purpose of this research is to explain the relationship between grammatical cohesion markers and lexical cohesion in advertising discourse that can support the formation of coherence. The data used comes from the Canmake Tokyo Japan advertisement. The data collection method used is the listening method with the basic technique, namely the tapping technique and the note-taking technique as a follow-up technique. The data analysis stage uses the commensurate method with the technique of sorting the determining elements (PUP). While the results of data analysis are presented using informal methods. Based on the results of data analysis, it can be seen that the cosmetic advertisements from Canmake Tokyo contain grammatical cohesion markers and lexical cohesion. Based on the appropriate use of cohesion markers, it can be seen that the discourse of Canmake Tokyo cosmetic advertisements is a discourse of coherence. The most common grammatical cohesion markers are reference and conjunction. While the most lexical cohesion markers found are repetition and synonyms.